The Setting-Intervention Fit of Nine Evidence-Based Interventions for Substance Use Disorders Within HIV Service Organizations Across the United States: Results of a National Stakeholder-Engaged Real-Time Delphi Study - Garner, Bryan R; Knudsen, Hannah K; Zulkiewicz, Brittany A; Tueller, Stephen J; Gotham, Heather J; Martin, Erika G; Donohoe, Tom; Toro, Alyssa K; Loyd, Katie; Gordon, Theodore (Journal of acquired immune deficiency syndromes (1999), 2022)
Given substance use disorders (SUDs) among people with HIV are highly prevalent, integrating SUD services within HIV service settings is needed to help end the HIV epidemic. In this study, we assessed the setting-intervention fit (SIF) of 9 evidence-based SUD interventions: acamprosate, disulfiram, oral naltrexone, injectable naltrexone, oral buprenorphine, injectable buprenorphine, contingency management, motivational interviewing, and cognitive behavioral therapy (CBT). Clinical and nonclinical HIV service organizations (HSOs) in the United States. In May 2020, a stakeholder-engaged real-time Delphi was completed with 202 HSOs. HSO respondents rated the extent to which each SUD intervention was fundable, implementable, retainable, sustainable, scalable, and timely for their HSO, and these 6 items were summed into an SIF score (possible range of 0-18). Motivational interviewing had the highest average SIF score (11.42), with SIF scores above the midpoint (9.5) for clinical (11.51) and nonclinical HSOs (11.36). For nonclinical HSOs, none of the other interventions were above the midpoint. For clinical HSOs, the average SIF scores were above the midpoint for CBT (10.97) and oral buprenorphine (9.51). Multivariate regression analyses, which controlled for characteristics of the HSO respondent, revealed geographic region of the United States and whether the HSO currently offered any substance use services as 2 of the best predictors of SIF scores. Notwithstanding the need to improve the SIF for the other evidence-based SUD interventions, motivational interviewing, CBT, and oral buprenorphine are currently the evidence-based SUD interventions with greatest perceived fit for integration within HSOs in the United States.